2022
DOI: 10.1002/chem.202202319
|View full text |Cite
|
Sign up to set email alerts
|

A Chemotactic Colloidal Motor

Abstract: Chemotaxis plays a crucial role in the realization of various functions of human life such as fertilization, immune function, inflammatory response, regeneration processes, etc. Inspired by the natural chemotaxis, colloidal motors with chemotactic ability can realize intelligent sense and targeted navigation, which bring a revolutionary method to biomedical applications like precision medicine. However, the application in the biomedical field requires the colloidal motors with submicrometer scale, strong chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Modifying the surface of the self-propelled particles (the particles that consume energy from chemical substances for their movements) [111,112] with atom-size metallic species will be another attractive subject for the future development of atomically dispersed nanocatalysts. In case of single-atom-layer catalysts, it is necessary to provide correlations between the numbers of the atomic layers and the catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Modifying the surface of the self-propelled particles (the particles that consume energy from chemical substances for their movements) [111,112] with atom-size metallic species will be another attractive subject for the future development of atomically dispersed nanocatalysts. In case of single-atom-layer catalysts, it is necessary to provide correlations between the numbers of the atomic layers and the catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15,51 ] The chemotaxis is ubiquitous in biology and can be easily achieved by establishing a non‐uniform reactant concentration gradient, which does not require expensive equipment and complex feed‐back regulation. [ 52 ] Thus, chemotaxis has been widely investigated. This part focuses on the design and biological applications of chemotactic MNMs, mainly involving catalytic and biohybrid MNMs ( Figure and Table 2 ).…”
Section: Design Strategies Of Biomedical Mnmsmentioning
confidence: 99%
“…Glucose activated chemotactic MNMs have been designed and the underlying mechanisms of chemotaxis have been experimentally revealed. [ 51a,52,65 ] By virtue of the catalysis of glucose oxidase (GOx) or cascade catalysis of GOx and CAT, chemotactic MNMs with different architectures were obtained, such as polymersome, polymer‐brush‐functionalized Janus gold (PNIPAM@JAu@GOx) nanomotor, and flask‐like colloidal motor. [ 12a,65,66 ] It was demonstrated that these MNMs could swim along the glucose gradient to reach the regions with higher glucose concentration, showing great potential in performing in vivo tasks.…”
Section: Design Strategies Of Biomedical Mnmsmentioning
confidence: 99%
“…The diminutive size, expansive surface area, and diverse functional attributes of micro/nanomotors (MNMs) confer a broad spectrum of applications and manipulation capabilities within microenvironmental interactions, nano-bio-interfaces, and cellular contexts [ 1 , 2 , 3 , 4 , 5 ]. Particularly in the biomedical field, intelligent MNMs have the potential to revolutionize drug delivery, cancer treatment, and in vivo imaging [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%